Secondary School Teachers’ Perceptions of Soft Skills Acquisition by Students in Bayelsa State - Ugolo, Stella Peremoboere; Oribhabor, Chinelo Blessing (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
In an increasingly changing, skill-based global economy, soft skills such as communication, teamwork, problem solving, adaptability, and emotional intelligence are essential to students' success in and out of the classroom. This study examines secondary school teachers' perceptions of students' acquisition of soft skills in secondary schools in Bayelsa State, Nigeria. A descriptive survey method was used in the study. Secondary school teachers in Bayelsa State comprised the population in the study. 200 teachers were sampled using a multi-stage sampling technique. Eight local government areas exist in Nigeria's Bayelsa State. Four out of the eight local government areas (LGAs) in the state were selected at random. Out of the eight local government areas (LGAs) of the state, four were sampled randomly. Ten secondary schools were randomly sampled from each of the chosen LGAs to yield the forty schools. Five teachers were intentionally sampled from each school, targeting those who have taught for at least three years and know their students' academic and social behaviors. The "Teachers' Perception on Soft Skills Acquisition Questionnaire (TPSSAQ)" is a self-constructed and validated tool utilized by the researchers. A reliability coefficient of 0.86 was attained by using Cronbach's alpha. A significance level of 0.05 was used to evaluate the hypothesis. Mean, standard deviation, and independent sampled t-test statistics were used in the data analysis. The results showed that despite teachers' positive attitude towards soft skills, students' acquisition rate is low due to lack of training, limited resources, time constraints, and lack of curriculum support. The study recommends updating secondary school curriculums to include soft skills as key learning outcomes.